Using Crime Script Analysis to Understand the Illegal Harvesting of Live Corals: Case Studies From Indonesia and Fiji. (August 2020) - Sosnowski, Monique C.; Weis, Judith S.; Petrossian, Gohar A.
Imported to adorn tanks of marine aquarium hobbyists, the trade in live corals poses a significant risk to species that concurrently face threats from rising global temperatures, pollution, and destructive fishing practices. To better understand the live coral trade, we employed a crime script framework to analyze the process by which corals are harvested in two of the world's major exporting countries—Indonesia and Fiji. We demonstrate that coral harvesting and export are complex activities that require a specific set of skills and tools. As such, various intervention strategies are proposed to address illegal coral harvesting at different stages of the crime script.